Neuroprotective Effects and Mechanisms of Zhenlong Xingnao Capsule in In Vivo and In Vitro Models of Hypoxia - Wei, Xia; Zhu, Qingfen; Liu, Na; Xu, Lihua; Wei, Sheng; Fan, Zhiyun; Sun, Changhua; Zhao, Yan; Qiao, Mingqi; Wu, Jibiao; Hu, Defu; Wang, Yang; et al. (Frontiers in Pharmacology, 2019)
Zhenlong Xingnao Capsule (ZXC) is a Tibetan medicine used to treat ischemic stroke. We aimed to clarify the role of ZXC in cerebral ischemia protection; reveal amino acid neurotransmitter changes in the frontal cortex after drug intervention; determine mRNA and protein expression changes in Bcl-2, Bax, caspase-3, P38, and nuclear factor (NF)-кB in the frontal cortex and changes in antioxidant indices in the brain; and elucidate the mechanisms underlying ZXC action.